Thermal wave resonant cavity technique in measuring thermal diffusivity of sucrose solution - Zakaria, Azmi; Sing, L. T.; Saion, Elias; Abdul Wahab, Zaidan (Universiti Putra Malaysia Press, 2006)
The thermal-wave resonant cavity technique has been used to measure thermal diffusivity of sucrose solution with precision up to three-significant-figure. The thermal diffusivity of the solution decreases linearly with the increase of sucrose weight percentage and agrees to the simple mixture rule in the range up to a saturated point. Also the solution thermal diffusivity varies linearly with square FWHM. The thermal diffusivity value of water is very close to the literature value.